パラグライダーのプロペラを研磨中に受傷した顔面裂傷の1例 - 石戸, 克尚; 冨原, 圭; 野口, 誠; 今上, 修一; 藤原, 久美子 (口腔顎顔面外傷 : 日本口腔顎顔面外傷学会誌, 2017)
The main causes of facial injuries are traffic accidents, falls, and blows. However, the use of professional rotating cutting instruments such as angle grinders is increasing in line with the popularity of do-it-yourself. There have been some reports on injuries caused by such tools. Sufficient protection is necessary because injuries with rotating cutting instruments are sometimes critical. Here, we report a case of a facial injury caused by using an angle grinder.A 61-year-old man was referred to our hospital in May 200X. The patient had been injured by being hit by a propeller of paraglider using an angle grinder. The wound involved from the left side of the nose root to the left side of the buccal and from the right side of the buccal to the chin. The left parotid duct was ruptured and the wound reached the sinus wall and alveolar bone.The patient was diagnosed with facial soft tissue injury, rupture of the left side of the parotid duct, and fracture of teeth roots, and underwent wound suture, repair of the parotid duct, and teeth extraction. Bone fracture of the left side of the sinus wall was observed but there were no signs of shift of occlusion. Parotid duct contrast radiography revealed good repair. However, scar contracture of the left side of the buccal wound was observed, so cicatrization was conducted 4 months after the operation.Facial injuries caused by rotating cutting instruments result in diverse wounds. When repairing facial injuries, not only functional recovery but also cosmetic recovery after operation is important.